Effects of pre-pregnancy body mass index on cardiometabolic biomarkers in pregnant emirati women - Lolowa A. Almekhaini; Shamsa A. Awar; Taoufik Zoubeidi; Sania Al Hamad; Javed Yasin; Junu V. George; Maha Khaled; Nehaya Qasem; Fatima Bahwan; Hassib Narchi; Elhadi H. Aburawi (Reproductive Health)
Abstract Background To study effect of pregnancy on obese women’s maternal cardiometabolic biomarkers as a signature for maternal morbidity and complications. Methods This cross-sectional cohort study involved pregnant Emirati women who had regular menstrual cycles and had normal blood pressure. Pre-pregnancy body mass index was calculated using height and weight measurements recorded within three months before current pregnancy. Average systolic and diastolic blood pressure measurements were calculated from each visit. Blood samples were collected randomly once and following cardiometabolic biomarkers were measured. Results We enrolled 178 pregnant women, with a mean age ± standard deviation of cohort was 29.9 ± 4.97 years and Pre-pregnancy body mass index 28.11 ± 6.58 kg/m2. None of blood pressure measurements or biomarkers serum concentrations were statistically different across Pre-pregnancy body mass index groups except for soluble intercellular cytoadhesive molecule-1levels which were the highest in underweight women. Pregnant women with pre-gestational obesity had higher systolic and diastolic blood pressure levels compared to women with normal or overweight. All variables were statistically significantly different by trimesters except systolic blood pressure, random blood glucose, lipoprotein-A, and high-sensitivity C-Reactive Protein. After adjusting, in a multivariate linear regression model, for maternal age, trimester of pregnancy, education level, parity and smoking, none of biomarkers or blood pressure were found to be significantly associated with Pre-pregnancy body mass index. In a multivariate linear regression model adjusting for maternal age, Pre-pregnancy body mass index, education level, parity and smoking, gamma-glutamyl transferase, total cholesterol, high density lipoprotein, low-density lipoprotein, triglycerides, apolipoprotein A & B, interleukin-6, tumor necrosis factor-alpha and insulin-like growth factor-1 concentrations remained significantly associated with advancing trimester of pregnancy. There was a significant interaction between Pre-pregnancy body mass index and trimester of pregnancy for serum gamma-glutamyl transferase and soluble intercellular cytoadhesive molecule-1concentration. Conclusion This study emphasizes how pregnancy has a significant impact on cardiometabolic markers in obese women, indicating both hyperlipidemic status of pregnancy and diabetogenic tendency in obese patients who are not diabetics. These findings may suggest that pregnancy in obese patients increases risk of developing metabolic syndrome in future, therefore more attention is recommended of pregnant obese women and further study of establishing specific cardiometabolic biomarkers screening program.